Randomised trial of cord clamping and initial stabilisation at very preterm birth. Issue 1 (18th September 2017) - Duley, Lelia; Dorling, Jon; Pushpa-Rajah, Angela; Oddie, Sam J; Yoxall, Charles William; Schoonakker, Bernard; Bradshaw, Lucy; Mitchell, Eleanor J; Fawke, Joe Anthony
Abstract : Objectives: For very preterm births, to compare alternative policies for umbilical cord clamping and immediate neonatal care. Design: Parallel group randomised (1:1) trial, using sealed opaque numbered envelopes. Setting: Eight UK tertiary maternity units. Participants: 261 women expected to have a live birth before 32 weeks, and their 276 babies. Interventions: Cord clamping after at least 2 min and immediate neonatal care with cord intact, or clamping within 20 s and immediate neonatal care after clamping. Main outcome measures: Intraventricular haemorrhage (IVH), death before discharge. Results: 132 women (137 babies) were allocated clamping ≥2 min and neonatal care cord intact, and 129 (139) clamping ≤20 s and neonatal care after clamping; six mother-infant dyads were excluded (2, 4) as birth was after 35 +6 weeks, one withdrew (death data only available) (0, 1). Median gestation was 28.9 weeks for those allocated clamping ≥2 min, and 29.2 for those allocated clamping ≤20 s. Median time to clamping was 120 and 11 s, respectively. 7 of 135 infants (5.2%) allocated clamping ≥2 min died and 15 of 135 (11.1%) allocated clamping ≤20 s; risk difference (RD) −5.9% (95% CI −12.4% to 0.6%). Of live births, 43 of 134 (32%) had IVH vs 47 of 132 (36%), respectively; RD −3.5% (−14.9% to 7.8%). There were no clear differences in other outcomes for infants or mothers. Conclusions: This is promising evidence that clamping after at least 2 min and immediate neonatal care with cord intact at very preterm birth may improve outcome; a large trial is urgently needed. Trial registration: ISRCTN 21456601 .